Zydzi w dawnej Rzeczypospolitej : materialy z konferencji "Autonomia zydow w Rzeczypospolitej Szlacheckiej" : 22-26 IX 1986 - Autonomia zydow w Rzeczypospolitej Szlacheckiej (1986 : Krakow, Poland); Link-Lenczowski, Andrzej; Polanski, Tomasz; Uniwersytet Jagiellonski. Miedzywydzialowy Zaklad Historii i Kultury Zydow w Polsce (Wroclaw : Zaklad narodowy im. Ossolinskich, 1991)
Papers from a national congress on the role of Jews in the old Polish Commonwealth.
Errata slip inserted.
Includes bibliographical references and indexes.
Keywords: Jews -- Poland -- History -- Congresses; Poland -- Ethnic relations -- History -- Conresses